Light-driven transformable optical agent with adaptive functions for boosting cancer surgery outcomes - Ji Qi (Nature Portfolio, 2018)
The combination of imaging techniques in cancer treatment often involves a trade-off in properties due to the opposite working mechanisms. Here, the authors report on a material that avoids the trade-off by switching from photoacoustic imaging to fluorescence imaging upon an external light trigger